2012
DOI: 10.4236/ijoc.2012.22020
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of 2-Amino-4,5,6,7-tetrahydrobenzo[<i>b</i>]thiophenes with Benzoyl-Isothiocyanate: Synthesis of Annulated Thiophene Derivatives and Their Antitumor Evaluations

Abstract: The reaction of the tetrahydrobenzo[b]thiophene derivatives 1a,b with benzoylisothiocyanate (2) afforded the thiourea derivatives 3a,b. Cyclization of the latter products gave the annulated products 4a,b. Compounds 3a,b reacted with either hydrazine hydrate (5a) or phenyl hydrazine (5b) afforded compounds 7a-d which underwent cyclization for compounds 7a,c afforded compound 9. On the other hand compounds 4a,b reacted with either hydrazine hydrate (5a) or phenyl hydrazine (5b) afforded compounds 6a-d a second p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Sharkawy et al [31] synthesized a series of thiophene incorporating pyrazolone moieties via diazo coupling of diazonium salt of 3-substituted-2-amino-4,5,6,7-tetrahydrobenzo[ b ]thiophenes with 3-methyl-1 H -pyrazol-5(4 H )-one, 3-methyl-1-phenyl-1 H -pyrazol-5(4 H )-one or 3-amino-1 H -pyrazol-5(4 H )-one, respectively as represented in Scheme 15. Newly synthesized derivatives were tested for cytotoxicity against the well known established model ehrlich ascites carcinoma cells (EAC) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Sharkawy et al [31] synthesized a series of thiophene incorporating pyrazolone moieties via diazo coupling of diazonium salt of 3-substituted-2-amino-4,5,6,7-tetrahydrobenzo[ b ]thiophenes with 3-methyl-1 H -pyrazol-5(4 H )-one, 3-methyl-1-phenyl-1 H -pyrazol-5(4 H )-one or 3-amino-1 H -pyrazol-5(4 H )-one, respectively as represented in Scheme 15. Newly synthesized derivatives were tested for cytotoxicity against the well known established model ehrlich ascites carcinoma cells (EAC) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…5) On the other side, the derivatives of tetrahydrobenzo [b] thiophene exist in many pharmaceutical applications such as anti-tumor, 6) antimicrobial, [7][8][9] antiviral, 10) anti-leishmanial agents, 11) antioxidant activity, 12) anti-arrhythmic, serotonin antagonist and anti-anxiety activities. 13) Recently we were involved through the synthesis of polyfunctional heterocyclic compounds, where the 2-cyanomethylbenzo[c] imidazole was used as the key starting compound.…”
mentioning
confidence: 99%
“…11) Triazoles, in particular, substituted 1,2,4-triazoles are among the various heterocycles that have received the most attention during the last decades as potential antimicrobial agents. [12][13][14] In spite of a large number of antibiotics and chemotherapeutics available for medical usage, the increasing demands make it necessary to continue the search for new antimicrobial substances. Though, various molecules were designed and synthesized for this aim, the efforts have demonstrated that 1,3-diazines and 1,2,4-triazoles could be considered as possible antimicrobial agents.…”
mentioning
confidence: 99%
“…The change of its carboxyl group to an amide group increased its bacteriostatic effects. 26,27) In the present investigation the authors synthesizes ethyl 2-(3-dodecanoylthioureido)-4,5,6,7-tetrahydrobenzo[b]-thiophene-3-carboxylate 3 from the reaction of lauroyl isothiocyanate 15,28) with o-aminoester derivative 13) as starting material. Compound 3 is utilized as a novel building block to give the target condensed 1,3-diazines and 1,3-thiazines via intramolecular exo-trig annulations as well as some 1,2,4-triazole derivatives bearing lauryl group hoping to increase their antimicrobial properties.…”
mentioning
confidence: 99%